Case Report: Infantile Bullous Pemphigoid: Triggering by COVID-19 Is Speculative - Rosińska-Więckowicz, Anna; Jałowska, Magdalena; Bowszyc-Dmochowska, Monika; Dmochowski, Marian (Frontiers in Medicine, 2021)
Bullous pemphigoid (BP) is a cutaneous disease triggering by numerous stimuli, in which genetic milieu-influenced autoimmunity to hemidesmosomal proteins, namely BP180 and /or BP230 initiates an inflammation leading to the dermal-epidermal junction enzymatic pathological remodeling. Here, to the best of our knowledge, we present the first case of an infantile BP apparently triggered by COVID-19. BP should be included in the differential diagnosis of infantile rashes showing blisters or vesicles or both as well as their prodromal and evolutionary lesions. Possible triggers, including COVID-19, of BP in infancy should be identified and properly dealt with.